Bilingualism and second language acquisition: a review - Karunakaran, T. (university of Jaffna, 2014)
In this paper, second language acquisition and bilingualism are focused and the relationship between these is broadly analyzed. An attempt was made to probe into the factors which influence the second language acquisition in bilingual contexts. This paper employed an analytical approach to explore the viewpoints of various scholars with regard to second language acquisition and bilingualism. In this regard, psycholinguistic issues, sociolinguistic issues, neuropsychological issues, bilingual education issues, issues of formal instruction, issues of language input and issues of teacher talk were analyzed. Besides these, the different learning models like interactional language learning, content-based language learning, and cooperative learning were analyzed to find out how best these models help the students acquire the second language. The analysis of research studies by different scholars made one thing very clear that bilingual children do acquire the languages very easily without encountering any major breakdowns in the process of acquisition.
Keywords: Bilingualism; Second language acquisition